Rework management in construction contracts : an assessment of NZS3910:2013 provisions : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering, Construction Project Management, Massey University, Auckland, New Zealand - Asadi, Ramin (Massey University, 2021)
Contracts play a significant role in achieving project goals in the construction industry. To enhance a project's performance by implementing a professional contract, construction practitioners must understand how contraction issues are addressed in the contract conditions. Although various contributing factors that affect construction contracts have been investigated and several methodologies have been proposed, the contract provisions that contribute to rework in construction projects have not been assessed adequately. Rework is of interest in the construction industry as it occurs throughout the project life cycle and affects its performance. The lack of understanding of construction practitioners under rework events may lead to cost overruns and delay in projects, resulting in contractual claims and disputes. Therefore, this research aims to investigate the contract clauses to improve the conditions that affect the project's performance by addressing rework. On the other hand, the contract is an essential means of controlling and managing interactions between parties under various situations. The assessment of contract provision in addressing contractual issues has been practiced effectively over the years to overcome conflicts between contract parties. Thus, the selected concept is helpful for improving the contract conditions under different circumstances. This study attempts to address issues related to rework in construction projects, which significantly improves the contract conditions. Initially, through conducting a comprehensive literature review, the root causes of rework are identified and then using a systematic literature review approach, the identified causes are classified with liable contract parties. The classified rework causes then are investigated in New Zealand construction projects using a questionnaire survey to find the relevant common causes of rework in contracts. The relationship between rework causes and contract clauses is then established through common sources of rework and contractual claims. For this purpose, the case of NZS3910 is selected as the most commonly used standard form of contract in New Zealand to assess the contract provisions under rework events. The initial findings show that the current condition of the contract does not address rework adequately. After investigating the relational aspect of rework in the construction contract, a series of professional interviews are conducted to explore the strengths and weaknesses of the contract conditions related to rework in construction projects. Then, the best practice to address rework is followed up. Furthermore, the current provisions stipulated in NZS3910 are evaluated as a documentary review to collect evidence for validation of interview results. It is observed that, while rework has not been defined in the contract, some of the contract clauses can be referenced for addressing rework. It is also confirmed that more clarification in the contract provision is required during contract preparation to avoid contractual claims originating from rework. Thus, the study develops a list of recommendations for improving the contract conditions that address rework issues. The research concludes by providing guidelines for addressing rework in contract provisions of NZS3910 and some general recommendations for improving the contract conditions. This research adds to the body of knowledge by improving the contract practices for rework management and achieving higher project performance with fewer contractual claims and disputes. Finally, and based on the study's findings, a framework that shows the flow of information for addressing rework is presented and recommended for further investigation in future research.
Keywords: Construction contracts; Standards; Construction projects; Management; New Zealand; 330202 Building construction management and project planning